Deciphering genetics underlying stable anaerobic germination in rice: phenotyping, QTL identification, and interaction analysis - Ghosal, Sharmistha; Casal, Carlos; Quilloy, Fergie Ann; Septiningsih, Endang M.; Mendioro, Merlyn S.; Dixit, Shalabh (Springer, 2019)
Anaerobic germination (AG) is an important trait for direct-seeded rice (DSR) to be successful. Rice usually has low germination under anaerobic conditions, which leads to a poor crop stand in DSR when rain occurs after seeding. The ability of rice to germinate under water reduces the risk of poor crop stand. Further, this allows the use of water as a method of weed control. The identification of the genetic factors leading to high anaerobic germination is required to develop improved DSR varieties. In the present study, two BC1F2:3 mapping families involving a common parent with anaerobic germination potential, Kalarata, an indica landrace, and two recurrent parents, NSIC Rc222 and NSIC Rc238, were used. Phenotyping was done under two environmental conditions and genotyping was carried out through the KASP SNP genotyping platform. A total of 185 and 189 individuals genotyped with 170 and 179 polymorphic SNPs were used for QTL analysis for the two populations, Kalarata/NSIC Rc238 and Kalarata/NSIC Rc222, respectively. A total of five QTLs on chromosomes 3, 5, 6, 7, and 8 for survival (SUR) and four QTLs on chromosomes 1, 3 (two locations), and 7 for the trait seedling height (SH) across the populations and over the screening conditions were identified. Except for the QTLs on chromosomes 5 and 8, the parent with AG potential, Kalarata, contributed all the other QTLs. Among the five QTLs for SUR, the second-largest QTL (qSUR6–1) was novel for AG potential in rice, showing a stable expression in terms of genetic background and screening conditions explaining 11.96% to 16.01% of the phenotypic variation. The QTL for SH (qSH1–1) was also novel. Considering different genetic backgrounds and different screening conditions, the QTLs identified for the trait SUR explained phenotypic variation in the range of 57.60% to 73.09% while that for the trait SH ranged from 13.53% to 34.30%